“Remotion” Total Wrist Arthroplasty: Preliminary Results of a Prospective International Multicenter Study of 215 Cases - Herzberg, Guillaume; Boeckstyns, Michel; Sorensen, Allan Ibsen; Axelsson, Peter; Kroener, Karsten; Liverneaux, Philippe; Obert, Laurent; Merser, Soren (Journal of Wrist Surgery, 2012)
This study reports the current results of an international multicenter study of one last generation total wrist arthroplasty (TWA) (“ReMotion,” Small Bone Innovation, Morristown, PA).The two first authors (G.H. and M.B.) built a Web-based prospective database including clinical and radiological preoperative and postoperative reports of “ReMotion” TWA at regular intervals. The cases of 7 centers with more than 15 inclusions were considered for this article.A total of 215 wrists were included. In the rheumatoid arthritis (RA; 129 wrists) and nonrheumatoid arthritis (non-RA; 86 wrists) groups, there were respectively 5 and 6% complications requiring implant revision with a survival rate of 96 and 92%, respectively, at an average follow-up of 4 years. Within the whole series, only one dislocation was observed in one non-RA wrist. A total of 112 wrists (75 rheumatoid and 37 nonrheumatoid) had more than 2 years of follow-up (minimum: 2 years, maximum: 8 years). In rheumatoid and non-RA group, visual analog scale (VAS) pain score improved by 48 and 54 points, respectively, and QuickDASH score improved by 20 and 21 points, respectively, with no statistical differences. Average postoperative arc of wrist flexion–extension was 58 degrees in rheumatoid wrists (loss of 1 degree) compared with 63 degrees in non-RA wrists (loss of 9 degrees) with no statistical differences. Grip strength improved respectively by 40 and 19% in rheumatoid and non-RA groups (p = 0.033). Implant loosening was observed in 4% of the rheumatoid wrists and 3% of the non-RA wrists with no statistical differences.A Web-based TWA international registry was presented. Our results suggest that the use of the “ReMotion” TWA is feasible in the midterm both for rheumatoid and non-RA patients. This is a significant improvement compared with the previous generation TWA. The level of evidence for this study is IV.
Keywords: total wrist arthroplasty; multicenter study; wrist arthrtitis; wrist arthrosis